Genetic evaluation of production potential of Black Bengal goat using frozen semen under community based rearing system - Ali, MY; Husain, SS; Bhuiyan, SA; Islam, MR; Haque, MA (Bangladesh Journal of Animal Science, 2016)
The objective of this study was to investigate production potential of Black Bengal goat using frozen semen under community based-rearing system. Forty Black Bengal does were distributed to the goat keepers and inseminated with frozen semen of selected Black Bengal bucks. Statistical analyses of all parameters were done using SAS. Genetic parameters were also measured using VCE software. Means along with standard errors for productive performance were 0.96±0.01, 4.25±0.06, 7.04±0.12 kg, 36.51±0.64, 31.29±0.98 g/d, and 247.80±3.13 ml/d, respectively for birth weight, body weight at 3- and 6-month, average daily gain at 3- and 6-month and daily milk yield. Reproductive performances were 1.81±0.107, 1.44±0.097, 145.33±0.649 days, 200.60±2.83 days, 7.69±1.97 kg, 40%, 19.65%, respectively for litter size, service per conception, gestation period, age and weight at first heat, conception rate and kid mortality. Effects of sex and litter size were significant (p<0.01) for birth and 3-month weight and season was significant (p<0.05) only for birth weight. Bucks showed significant effects (p<0.05) for birth and 3-month weight. Estimated heritability for birth, 3- and 6-month weight were 0.21±0.03, 0.36±0.07 and 0.12±0.05. Genetic correlations among body weights ranged from 0.35 to 0.65 and phenotypic correlations ranged from 0.44 to 0.52. Therefore, the AI program with frozen semen of Black Bengal buck would be beneficial to the farmers. Bang. J. Anim. Sci. 2016. 45 (2): 52-59